2016
DOI: 10.3928/00904481-20160113-01
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Pediatrics

Abstract: A 16-year-old Hispanic girl with an elevated body mass index in an otherwise normal state of health presented for her well-child examination. She had signs of metabolic syndrome and insulin resistance including increased waist circumference and acanthosis nigricans. Laboratory results revealed elevated transaminases with otherwise normal hepatic function. Based on the physical examination and laboratory results, she was diagnosed with nonalcoholic fatty liver disease (NAFLD). After further evaluation, she even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Nonalcoholic fatty liver disease (NAFLD) is a generic term for a wide spectrum of disease that ranges from fatty liver to advanced fibrosis and cirrhosis to hepatocellular cancer and end-stage liver failure. A study of childhood and adolescent liver epidemiology showed NAFLD in 9.6% of children between age 2 and 19 years [64]. However, Xanthakos et al [65] evaluated the prevalence of NAFLD in children undergoing MBS in the Teen-LABS population.…”
Section: Obesity Disease-related Co-morbidities and Outcomesmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a generic term for a wide spectrum of disease that ranges from fatty liver to advanced fibrosis and cirrhosis to hepatocellular cancer and end-stage liver failure. A study of childhood and adolescent liver epidemiology showed NAFLD in 9.6% of children between age 2 and 19 years [64]. However, Xanthakos et al [65] evaluated the prevalence of NAFLD in children undergoing MBS in the Teen-LABS population.…”
Section: Obesity Disease-related Co-morbidities and Outcomesmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in children and adolescents in the United States [ 1 4 ] with up to 38% of obese children affected [ 5 ]. Prevalence increases with age, reaching approximately 17.5% in adolescents [ 5 ], and with 5 times the risk of fatty liver in Hispanics [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…No se encontraron estudios en la literatura que midieran la prevalencia de esteatosis hepática en los pacientes con niveles bajos de vitamina D, en nuestro análisis fue del 13.5%, cifra que si se compara con la prevalencia aislada de EHGNA que va del 3 al 12.6% en la población pediátrica en general ( Uppal 2016, Duncan 2016, Flores 2004 y Clemente 2016) y que aumenta hasta 40-70% en obesos (Duncan 2016), por lo que vale la pena profundizar en la asociación entre estas dos variables.…”
Section: Discussionunclassified
“…Sugerimos implementar un método diagnóstico por imagen con mayor sensibilidad como la elastografía por ultrasonido la cual se encuentra en vías de sumarse a las recomendaciones de las guías internacionales pediátricas (Duncan 2016).…”
Section: Discussionunclassified